The Forms and Analysis of Product Placement - Hlaváček, Josef (2015)
The aim of this thesis is to describe marketing communication and product placement in the theoretical part, consequently analyze examples of product placement from the practice and last but not least also analyze the perception and examples of product placement based on the survey research. Therefore the thesis is divided into three main parts. The first, theoretical part, describes the marketing mix, concept of communication, communication mix, new forms of communication, integrated marketing communication, history of product placement, legal framework in the Czech Republic and the forms of product placement. The practical part then focuses on concrete examples of product placement in selected industries (namely TV shows and series, music videos, publishing and novels and computer games) followed by real offers of product placement in the Czech market -- concretely offerings within TV shows of Czech TV channels of Česká televize, Nova and Prima. The third part of the thesis analyses perception of product placement and examples of good and bad product placement based on personal questionnaires. In conclusion, there is an evaluation of the presented information and overview of the survey findings.